The impact of geogebra integration into problem-based learning on mathematics learning outcomes based on students' learning interest - Reni Widya Putri; Sri Sutarni (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2025)
This study aimed to examine how the integration of GeoGebra in problem-based learning influences mathematics learning outcomes, taking into account students' learning interest. The study was motivated by low student achievement and the limited use of technological innovation in mathematics instruction. A quasi-experimental method with a Post-Test Only Control Group Design was employed, using a quantitative approach. The participants were 9th-grade students at SMP Muhammadiyah 5 Surakarta. Two classes were selected through cluster random sampling to represent the overall 9th-grade population. The sample consisted of class IX-C, which served as the control group and received PBL without GeoGebra, and class IX-D, which served as the experimental group and received PBL integrated with GeoGebra. The research instruments included a learning interest questionnaire and a mathematics learning outcome test. Data were collected through a post-test and a questionnaire using a 4-point Likert scale. A two-way analysis of variance (ANOVA) with a 2Ã—2 factorial design was used for data analysis. The findings indicated that: (1) the integration of GeoGebra into the PBL model had a significant effect on students' mathematics learning outcomes; (2) students' learning interest significantly influenced their learning outcomes; and (3) there was no significant interaction effect between the learning model and learning interest. These results suggest that applying PBL with GeoGebra is an effective instructional innovation in mathematics teaching, particularly for the topic of Similarity, and that the integration of GeoGebra can enhance students' mathematics learning outcomes.